DAMPAK POSITIF DAN NEGATIF PERMAINAN GAME ONLINE DIKALANGAN PELAJAR - Suryanto, Rahmad Nico; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Online games users who have high self-control is able to regulate the use of online games that are not immersed in online games, are able to use online games as needed, able to integrate online activities with other activities in their lives. Instead, users of online games with low self-control is not able to direct and regulate his online behavior. They are not able to interpret stimuli encountered, and not able to choose the appropriate action. Based on the problems described above, the authors are interested in conducting research with the title: